2005
DOI: 10.1097/01.mcg.0000180636.74387.e6
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Pancreas

Abstract: Squamous cell carcinoma of the pancreas is a rare condition. The incidence has been estimated at approximately 1% of all pancreatic malignancies. The histogenesis is uncertain, but it has been proposed to originate from areas of squamous metaplasia of pancreatic ductal epithelium. We present a case of a 56-year-old man who presented with back pain and was found to have a squamous cell carcinoma of the pancreas without evidence of metastatic disease. Three months after en bloc resection with negative margins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 17 publications
1
56
1
4
Order By: Relevance
“…Other studies revealed that 92% of pancreatic squamous cell carcinomas occur in patients over the age of 50 years 2,9,13 . The analysis of the 25 cases did not show a significant sex preference (there were 14 men and 11 women in the group) 5 , and so pancreatic squamous cell carcinoma seems to affect both sexes equally.…”
Section: Figure 1 Hepatic Biopsy Showing Normal Liver In Lower Quadramentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies revealed that 92% of pancreatic squamous cell carcinomas occur in patients over the age of 50 years 2,9,13 . The analysis of the 25 cases did not show a significant sex preference (there were 14 men and 11 women in the group) 5 , and so pancreatic squamous cell carcinoma seems to affect both sexes equally.…”
Section: Figure 1 Hepatic Biopsy Showing Normal Liver In Lower Quadramentioning
confidence: 99%
“…It has various reported incidence rates, ranging from 0.5% to as high as 5% of pancreatic ductal carcinoma 2,4,5-13 . Halpert and his group (as quoted by Brown et al) in their series of 120 patients, described an incidence rate of 5% pure squamous pathology 5 . However, in a much larger series review such as Baylor and Berg (5075 patients), the reported incidence of pure squamous cell carcinoma was 0.5% of the pancreatic ductal carcinomas 14 .…”
Section: • Connective Tissue Origin • Uncertain Histogenesismentioning
confidence: 99%
See 3 more Smart Citations